Implications of the Patient-Centered Medical Home for Nursing Practice. (November 2015) - Stewart, Kenda R.; Stewart, Greg L.; Lampman, Michelle; Wakefield, Bonnie; Rosenthal, Gary; Solimeo, Samantha L.
Abstract : OBJECTIVE: The experiences of RNs and licensed practical nurses (LPNs) implementing a patient-centered medical home (PCMH) in the Department of Veterans Affairs (VA) primary care clinics were examined to understand model implications for nursing practice and professional identity. BACKGROUND: National implementation of the PCMH model, called patient-aligned care teams (PACTs) in VA, emphasizes areas of nursing expertise, yet little is known about the effect of medical homes on the day-to-day work of nurses. METHODS: As part of a formative evaluation to identify barriers and facilitators to PACT implementation, we interviewed 18 nurses implementing PACT. RESULTS: Challenges to nurse's organizational and professional roles were experienced differently by RNs and LPNs in the following areas: (1) diversified modes of care and expanded clinical duties, (2) division of labor among PACT nurses, and (3) interprofessional status in the team. CONCLUSIONS: Healthcare managers implementing PCMH should consider its inherent cultural and practice transformations.